O PAPEL DAS PUBLICAÇÕES E DOS COLPORTORES NA INSERÇÃO DO ADVENTISMO NO BRASIL - Carnassale, Helio (2015)
This research is about an investigation to assess the role of publications, literature evangelist and literature evangelism in the insertion of Adventism in Brazil. The aim is to identify the effects of the printing press and the importance of the printed page for the Protestantism, as well as to examine the missiological purposes that marked the emergence of the Publishing Ministry, the literature evangelism and literature evangelists in the emergent Adventist Church. This study also intents to establish the concepts of the theology of mission, the growth process and finally the Adventists missionary advancement in the context of the Protestant expansion of the second half of the 19th century, both worldwide and in South America. In addition to these objectives, this research presents the arrival of Protestantism in Brazil and aims to analyze as the German immigration contributed to the Adventist achieve their missional purposes, since the first publications were printed in German and came to the colonies this ethnic-linguistic origin. Based on this research proposal, our intention is clearly show the role of publications and literature evangelists in the establishing process of the Adventist Church in Brazil. This study used the historical method, with data collection through documental and bibliographic research and the study is defined as qualitative, basic and exploratory.